Passion fruit seed extract protects hydrogen peroxide-induced cell damage in human retinal pigment epithelium ARPE-19 cells - Haruka Uozumi; Shinpei Kawakami; Yuko Matsui; Sadao Mori; Akira Sato (Scientific Reports)
Abstract Age-related macular degeneration (AMD) is a major cause of vision loss among adults. We investigated the protective effects of passion fruit seed extract (PFSE) and its rich polyphenol piceatannol in an AMD cell model in which human retinal pigment epithelial ARPE-19 cells were exposed to hydrogen peroxide (H2O2). Using a cell viability WST-8 assay, we revealed that PFSE and piceatannol increased the cellular viability of ARPE-19 cells by 130% and 133%, respectively. Moreover, PFSE and piceatannol recovered the cell viability of ARPE-19 cells, which had decreased to 60% owing to H2O2-induced damage, to approximately 84% and 89%, respectively. In addition, we found that the treatment of ARPE-19 cells with H2O2 decreased the mitochondrial and glycolytic ATP production rate to approximately 54% that of healthy control ARPE-19 cells using a Seahorse extracellular flux analyzer. Furthermore, pretreatment with PFSE and piceatannol restored the oxidative stress-induced decrease in the mitochondrial and glycolytic ATP production rate to approximately 97% and 82%, respectively. These results indicated the cytoprotective effects of PFSE and piceatannol against oxidative stress in human ARPE-19 cells by resolving the dysfunction of mitochondrial and glycolytic energy metabolism.